Avaliação de equipes de desenvolvimento de software por meio de métricas orientadas a objeto - Madureira, Jamille Silva (2017)
Managing a software project is an increasingly complex task as the demands on the final product increase. Competitive environment in software industry and customer needs require software developers to increasingly concern themselves with user satisfaction as a measure of quality of the final product. Therefore, e ective management is required from project design up to software maintenance. The development team is one of the most relevant resources for the success of projects, but it is also where the greatest problems are found. Using metrics is a way to help the project team to achieve its goals and objectives. The goal of this work was to use software metrics to evaluate teams and and their members in order to analyze current performance of developers. To reach this objective, literature review and case study were applied as research instruments. The literature review allowed to discover reference values for the applied metrics in order to establish criteria that served as a basis to evaluate the software involved in the research. After obtaining this knowledge, the case study was applied to two local public companies and undergraduate students from two universities. In total, thirteen softwares were evaluated, four of which were developed in companies and nine by students. A tool was selected to collect software metrics automatically and to provide the result in a format ready to be manipulated. As a result, it was verified that the evaluation of software quality by means of metrics contributes to project management, because it indicates its failures and where it should be improved. Evidence has also been discovered that using collected software metrics is useful in evaluating development team members. By means of the case study, it was discovered that team composition is important to the success of the project, and that training and experience of the members directly a ect quality of software. When analyzing the software through metrics, it was observed that the best performance was achieved by developers with more advanced training and more near experience time. In this sense, software metrics can contribute to follow both the development of the project and the decisions that cause changes in the team.